Information technology law / Diane Rowland and Elizabeth Macdonald - "Rowland, Diane" (London, 1997)
This book presents students with the legal response to the challenges of innovations in information technology. It considers the impact of these developments on such areas as criminal law, evidence, tort, contract and intellectual property. The book provides a comprehensive array of cases and materials in the field. While it is aimed at students on undergraduate and postgraduate courses on information technology law, it may also be of interest at a more general level to practitioners and others whose business relies on modern information technology.
Keywords: Computers-law and legislation-Great Britain